2020
DOI: 10.17220/mojet.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Online Gaming Addiction Level Among University Students in Terms of Emotional Schemas, Agentic Personality, and Various Variables

Abstract: The aim of this study is to examine online game addiction level among university students in terms of emotional schemas, agentic personality, and various variables (i.e. gender, type of game played, and accommodation). The sample group consists of 380 university students studying in İzmir province and playing online games during the school year of 2017 and 2018. The data have been collected through multiple tools that are Online Game Addiction Scale for University Students, Multi-measure Agentic Personality Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Female students spend less time playing video games. The findings of this study are consistent with that of [17,25,26,27,28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Female students spend less time playing video games. The findings of this study are consistent with that of [17,25,26,27,28,29].…”
Section: Discussionsupporting
confidence: 91%
“…Although denial of emotions was higher in patients with high anxiety symptoms, as expected, our study showed that denial of emotions had a reducing effect on the occurrence of anxiety symptoms. In a study examining the relationship between Internet addiction and emotional schemas in Turkey, the Denial of Emotions schema was found to have a negative and significant relationship with Internet addiction [27]. It was stated that online gaming addiction had a hypnotic effect and although one did not realize the emotions and the effect it had, a negative relationship might occur through glorifying the feeling of success and competition [27].…”
Section: Emotional Schemasmentioning
confidence: 99%
“…In a study examining the relationship between Internet addiction and emotional schemas in Turkey, the Denial of Emotions schema was found to have a negative and significant relationship with Internet addiction [27]. It was stated that online gaming addiction had a hypnotic effect and although one did not realize the emotions and the effect it had, a negative relationship might occur through glorifying the feeling of success and competition [27]. Another study conducted in our country, that examined emotional schemas and defense mechanisms, showed that there was a significant inverse relationship between denial of emotions and immature and neurotic defenses [28].…”
Section: Emotional Schemasmentioning
confidence: 99%
“…The use of digital technologies creates convenience and differences in our lives, but their unconscious use can also create some negative effects (Aydemir, 2020). Technology such as the internet, computers, and mobile phones have many negative physiological or psychological effects, especially on individuals (Bekir, 2019). It is common for users to experience addictions (such as gaming, internet use, phone use), harmful content, cyberbullying, cyberfraud, and cybe harassment in this area (Hasebrink, Livingstone, Haddon & Olafsson, 2009; Van den Heuvel, Van den Eijnden, Van Rooij and Van de Mheen, 2012;Ybarra, 2004).…”
Section: Introductionmentioning
confidence: 99%